(untitled) (International Journal of Engineering and Computer Science, 2020)
Performance prediction of students in university courses is a crucial concern to all higher education institutions managements where several factors may affect their students’ performance. In Computer Science related programs, programming courses and having the skills of algorithm analysis are made compulsory subjects in most institutions of learning. Having mathematical skills play a vital role to be a good programmer and algorithm analysis. In this study an attempt was made to build a model which predict the performance of students in the Algorithm Analysis based on their grades of other courses, specifically by evaluating preliminary programming courses and different mathematics courses of the curricula. The data was collected from Wolkite University, Computing and Informatics College of Computer Science under graduate students of 2015-2018 batch students. To build the model classification algorithms, namely, Decision tree, Naïve Bayes and Support Vector Machine (SMO) were applied using Weka machine learning tool. The experiment from the study shows that a priori knowledge of the Data structure and Algorithm and Fundamentals of Programming I are essential to excel in the course Algorithm Analysis for computer science students. This work will be of considerable importance in identifying students who has low performance on this courses and the students will be advised to take action on their skill gap in timely manner. Finally, the classification algorithms were tested and performances comparison were made. The decision tree (J48) algorithm provides a promising result of 78.313%.